Optimized utilization of Salix—Perspectives for the genetic improvement toward sustainable biofuel value chains. Issue 10 (18th August 2022) - Rönnberg‐Wästljung, Ann Christin; Dufour, Louis; Gao, Jie; Hansson, Per‐Anders; Herrmann, Anke; Jebrane, Mohamed; Johansson, Ann‐Christine; Kalita, Saurav; Molinder, Roger; Nordh, Nils‐Erik; Ohlsson, Jonas A.; Passoth, Volkmar; et al.
Abstract: Bioenergy will be one of the most important renewable energy sources in the conversion from fossil fuels to bio‐based products. Short rotation coppice Salix could be a key player in this conversion since Salix has rapid growth, positive energy balance, easy to manage cultivation system with vegetative propagation of plant material and multiple harvests from the same plantation. The aim of the present paper is to provide an overview of the main challenges and key issues in willow genetic improvement toward sustainable biofuel value chains. Primarily based on results from the research project "Optimized Utilization of Salix " (OPTUS), the influence of Salix wood quality on the potential for biofuel use is discussed, followed by issues related to the conversion of Salix biomass into liquid and gaseous transportation fuels. Thereafter, the studies address genotypic influence on soil carbon sequestration in Salix plantations, as well as on soil carbon dynamics and climate change impacts. Finally, the opportunities for plant breeding are discussed using willow as a resource for sustainable biofuel production. Substantial phenotypic and genotypic variation was reported for different wood quality traits important in biological (i.e., enzymatic and anaerobic) and thermochemical conversion processes, which is a prerequisite for plant breeding. Furthermore, different Salix genotypes can affect soil carbon sequestration variably, and life cycle assessment illustrates that these differences can result in different climate mitigation potential depending on genotype. Thus, the potential of Salix plantations for sustainable biomass production and its conversion into biofuels is shown. Large genetic variation in various wood and biomass traits, important for different conversion processes and carbon sequestration, provides opportunities to enhance the sustainability of the production system via plant breeding. This includes new breeding targets in addition to traditional targets for high yield to improve biomass quality and carbon sequestration potential. Abstract : Bioenergy will be one of the most important renewable energy sources in the conversion from fossil fuels to bio‐based products. Short‐rotation‐coppice Salix could be a key player in this conversion since Salix has rapid growth, positive energy balance, an easy to manage cultivation system with vegetative propagation of plant material and multiple harvests from the same plantation. The paper provides an overview of the main challenges and key issues in willow genetic improvement towards sustainable biofuel value chains.